Síntese da gramática tensiva (Significação: Journal of Audiovisual Culture, 2006)
We present in this work three maio theses that could sound a little bit unsettling. First, not only do we invite affectivity to play some role in meaning production, but moreover, in the name ofHjelmslev's principie of immanence, we assume it to direct the production of meaning. Second, we suggest topping off structuralist semiotics o f oppositions with a semiotics o f intervals in which primacy is given to affectivity, inasmuch as ou r experiences are, above ali, measures, if not measures only. Finally, we try to show that both points mentioned presuppose the central role of the event, as well as the fascination of discourse for the concessive dimension of the event. Once admitted, these preliminaries tend to help detaching semiotics from the narrative, bringing it closer to tropological rhetoric instead.